Risk factors for typhoid fever in children in squatter settlements of Karachi: A nested case-control study - Fahad Javaid Siddiqui; Syed Rizwan Haider; Zulfiqar Ahmed Bhutta (Elsevier, 2008)
Summary: Typhoid fever remains a major public health problem in developing countries such as Pakistan. A great majority of cases occur in children living in poor sanitary conditions in squatter settlements in large cities. We conducted a case-control study to identify risk factor for typhoid fever in children under the age of 16 years residing in squatter settlements of Karachi. We enrolled 88 typhoid fever patients, diagnosed by positive blood culture or Typhidot® test, between June 1999 and December 2001. Simultaneously, we enrolled 165 age-matched neighborhood controls. Multivariate analysis done through conditional binary logistic regression analysis technique showed that increasing number of persons in the household (odds ratio [OR] = 1.9; 95% confidence interval [CI] 1.2-3.1), non-availability of soap near hand washing facility (OR = 2.6; 95% CI 1.1-6.3), non-use of medicated soap (OR = 11.2; 95% CI 1.3-97.6) and lack of awareness about contact with a known case of typhoid fever (OR = 3.7; 95% CI 1.6-8.4) were independent risk factors of the disease. Health education with emphasis on hand washing may help decrease the burden of typhoid fever in developing countries. Keywords: Typhoid, Risk factors, Case-control, Pakistan, Children